Intercropping effects on productivity and profitability of maize (Zea mays L) in Indo-Gangetic Plains of India - Seema Sepat,; Pardeep Kumar,; S.D. Bamboriya, (Annals of Agricultural Research, 2024)
Intercropping of maize can be a suitable option for effectively utilizing resource-use efficiency. Therefore, an experiment was conducted at Ludhiana to assess the biomass productivity and profitability having sole maize, maize + sweet sorghum (2:1), maize + pearl millet (2:1), maize + barnyard millet (2:2), maize + proso millet (2:2), maize + finger millet (2:2), maize + little millet (2:2) and maize + cowpea (2:2). The dry matter accumulation in maize was recorded higher in sole maize compared to other intercropped systems. Higher fresh biomass of maize and total (maize + intercrops) was recorded with maize + cowpea (2:2) followed by maize + pearl millet (2:1) and maize + sorghum (2:1) during kharif and spring seasons. In intercrops, pearl millet and sweet sorghum recorded higher fresh biomass yields in both seasons. An increase of 66.0 and 50.0% in fresh biomass was found with maize + cowpea (2:2) compared to sole maize in spring and kharif season, respectively. In spring, total (maize + intercrop) dry biomass was increased with maize + cowpea (2:2) by 40.82% compared to sole maize. Likewise, in the kharif season, the increase was 48.77% with maize + cowpea (2:2) than sole maize. Maize + cowpea intercropping recorded a higher B:C ratio followed by maize + pearl millet and maize + sorghum in both seasons. It may be concluded from the study that maize intercropping with cowpea (2:2) was found to enhance biomass productivity and profitability and proved to be a suitable option for the Indo-Gangetic Plains of India.